2022
DOI: 10.3389/fpubh.2022.1053873
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of the compulsory universal testing scheme in Hong Kong: Mathematical simulations of a household-based pooling approach

Abstract: This study aims to propose a pooling approach to simulate the compulsory universal RT-PCR test in Hong Kong and explore the feasibility of implementing the pooling method on a household basis. The mathematical model is initially verified, and then the simulation is performed under different prevalence rates and pooled sizes. The simulated population is based in Hong Kong. The simulation included 10,000,000 swab samples, with a representative distribution of populations in Hong Kong. The samples were grouped in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…In the nested pooling strategy, the samples in a positive pool are divided into smaller pools with an optimal number of stages, and the optimal pool size of each stage is calculated according to various measures such as the predicted number of positives and time limit [ 68 , 69 ]. Ng et al [ 70 ] conducted simulations of a household-based sequential pooling approach to optimize a universal testing scheme in Hong Kong. They showed that the household-based sequential pooling approach could rapidly screen people in high-risk groups for COVID-19 infections and quarantine those who tested positive [ 70 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the nested pooling strategy, the samples in a positive pool are divided into smaller pools with an optimal number of stages, and the optimal pool size of each stage is calculated according to various measures such as the predicted number of positives and time limit [ 68 , 69 ]. Ng et al [ 70 ] conducted simulations of a household-based sequential pooling approach to optimize a universal testing scheme in Hong Kong. They showed that the household-based sequential pooling approach could rapidly screen people in high-risk groups for COVID-19 infections and quarantine those who tested positive [ 70 ].…”
Section: Resultsmentioning
confidence: 99%
“…Ng et al [ 70 ] conducted simulations of a household-based sequential pooling approach to optimize a universal testing scheme in Hong Kong. They showed that the household-based sequential pooling approach could rapidly screen people in high-risk groups for COVID-19 infections and quarantine those who tested positive [ 70 ]. Although these approaches reduce the number of tests required, the operability of such strategies for time-critical epidemic control should be carefully assessed.…”
Section: Resultsmentioning
confidence: 99%